INOVASI TEKNOLOGI MENUJU ZERO WASTE PENANGANAN DARURAT SAMPAH DI KOTA MAGELANG - Kumalasari, Reta (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
The problem of domestic waste has become quite serious, considering the volume and rate of accumulation are increasing with the increasing population and economic activities. The Final Waste Disposal Site (TPSA) in Magelang City is currently overloaded because Magelang City only has one Final Waste Disposal Site (TPSA). If strategic and appropriate steps are not taken to reduce the waste entering the Banyu Urip Final Waste Disposal Site (TPSA), then within a maximum of 1-2 years the Banyu Urip Final Waste Disposal Site (TPSA) will not be able to receive waste shipments from Magelang City. The incomplete resolution of waste in Magelang City is due to the unavailability of waste processing technology that produces zero waste and is environmentally friendly. The policy analysis evaluation approach used is the Grid Analysis (Matrix Analysis) method. The results of the study recommend the application of waste processing machine technology by the Environmental Service. This mechanization technology is expected to be able to replace the previous method (open dumping and landfill) with waste mechanization with the advantages of being relatively odorless, relatively no social conflict and saving land. The mechanization technology consists of waste sorting machines, plastic shredding machines, organic waste pulping machines, conveyors and incinerators.